Material properties and strain distribution patterns of bovine growth plate cartilage vary with anatomic location and depth. (March 2022) - Fischenich, Kristine M.; Schneider, Stephanie E.; Neu, Corey P.; Payne, Karin A.; Ferguson, Virginia L.
Abstract: The aim of this study was to assess the bulk material properties and depth-dependent strain distribution of bovine growth plate cartilage. We hypothesized that both moduli and strain distribution are highly depth-, orientation-, and location-dependent. Bovine proximal tibiae (1-month-old) were sliced along the sagittal and coronal planes to create ∼ 4 mm 2 samples. Digital image correlation (DIC) was combined with stress relaxation tests for evaluation of bulk modulus (tangent and equilibrium) and depth-dependent strain distribution. A subset of samples was imaged after Col-F staining as well as histological staining (Safranin-O/Fast Green) to evaluate zonal organization and matrix composition. The mean tangent modulus was 4.25 ± 2.46 MPa while the equilibrium modulus was 0.86 ± 0.46 MPa. No significant differences in moduli were found with respect to orientation (sagittal vs coronal face), but sagittal location within the joint was a significant predictor for tangent modulus. Overall moduli values decreased from the periphery to the midline of the joint. Depth-dependent cellular organization, determined by cell density and shape, was highly variable. This heterogeneity may be a biological toughening mechanism. Peak normalized strains were observed most often in the hypertrophic zone. Modulus was significantly lower in the hypertrophic zone as compared to the resting and proliferative zones. This study is the first to evaluate moduli and strain distribution in intact growth plates as a function of depth, orientation, and anatomic location. Future work with growth plate tissue engineering should consider the location- and depth-dependent nature of the native tissue mechanical properties when designing mimetic constructs.